Estimates of the bivariate distribution function at quantile points - Butler, Calvin Charles, author; Siddiqui, Mohammed Moinuddin, 1928-, advisor; Boes, Duane C., committee member; Bailey, H. R., committee member (Colorado State University. Libraries, 1966)
To view the abstract, please see the full text of the document.
Keywords: Mathematical statistics